2021
DOI: 10.2144/fsoa-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Oncology in a Mouse: concepts, Models and Limitations

Abstract: The utilization of suitable mouse models is a critical step in the drug discovery oncology workflow as their generation and use are important for target identification and validation as well as toxicity and efficacy assessments. Current murine models have been instrumental in furthering insights into the mode of action of drugs before transitioning into the clinic. Recent advancements in genome editing with the development of the CRISPR/Cas9 system and the possibility of applying such technology directly in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Patient-derived xenografts (PDXs) typically involve implanting patient tumor cells in immunodeficient mice; immunocompromised mice are necessary to prevent rejection of human tumor cells by the host animal’s immune system and improve engraftment success rates ( 37 ). Tumor cells are implanted subcutaneously or orthotopically, and tumor growth as well as drug response is followed using calipers and fluorescent or bioluminescent imaging, along with pharmacokinetic and pharmacodynamic parameters ( 37 ). Implantation technique is important to consider as morphologic, interactome, and metabolic differences have been observed between tumors implanted orthotopically and those implanted subcutaneously ( 38 , 39 ).…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient-derived xenografts (PDXs) typically involve implanting patient tumor cells in immunodeficient mice; immunocompromised mice are necessary to prevent rejection of human tumor cells by the host animal’s immune system and improve engraftment success rates ( 37 ). Tumor cells are implanted subcutaneously or orthotopically, and tumor growth as well as drug response is followed using calipers and fluorescent or bioluminescent imaging, along with pharmacokinetic and pharmacodynamic parameters ( 37 ). Implantation technique is important to consider as morphologic, interactome, and metabolic differences have been observed between tumors implanted orthotopically and those implanted subcutaneously ( 38 , 39 ).…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%
“…Implantation technique is important to consider as morphologic, interactome, and metabolic differences have been observed between tumors implanted orthotopically and those implanted subcutaneously ( 38 , 39 ). One major benefit of the PDX model is that the patient’s stroma is initially preserved and implanted into the mouse model, though it is ultimately replaced with a murine stroma over time ( 37 ). The PDX model provides a 3D in vivo perspective, recapitulates tumor heterogeneity, and allows for measurement of pharmacokinetic and pharmacodynamic parameters.…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, toxic chemical oncogenesis screening using GEMMs might be a good strategy to find mutations which drive or repress cancer progression. The GEMMs with the KRAS mutation should be precancerous or have low aggressiveness and is suitable to assess additional mutations introduced by toxic agents that promote cancer onset and aggressiveness such as metastasis (Long et al, 2021). Once mutations related to cancer onset, dissemination, and metastasis are identified, the gene and its peripheral signal molecules might serve as a druggable targets to repress cancer.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…1 The failure rate through the pre-clinical stages of drug development can be high and many candidate molecules taken forward to clinical trials subsequently fail to recapitulate the safety profile and efficacy found in animal studies. [2][3][4][5] There are many reasons for this, but significant species differences in drug metabolism between animals (rats, mice) and humanswith concomitant changes in pharmacokinetics, metabolite profiles, toxicokinetics and pharmacodynamicsare key components underlying the observed failure rates. 5 We have developed a sophisticated transgenic mouse model in which the major human drug metabolising enzymesand the transcription factors regulating their expressionreplace their mouse counterparts.…”
Section: Introductionmentioning
confidence: 99%